Microbial Consortium with High Cellulolytic Activity (MCHCA) for Enhanced Biogas Production - Poszytek, Krzysztof; Ciezkowska, Martyna; Sklodowska, Aleksandra; Drewniak, Lukasz (Frontiers in Microbiology, 2016)
The use of lignocellulosic biomass as a substrate in agricultural biogas plants is very popular and yields good results. However, the efficiency of anaerobic digestion, and thus biogas production, is not always satisfactory due to the slow or incomplete degradation (hydrolysis) of plant matter. To enhance the solubilization of the lignocellulosic biomass various physical, chemical and biological pretreatment methods are used. The aim of this study was to select and characterize cellulose-degrading bacteria, and to construct a microbial consortium, dedicated for degradation of maize silage and enhancing biogas production from this substrate. Over one hundred strains of cellulose-degrading bacteria were isolated from: sewage sludge, hydrolyzer from an agricultural biogas plant, cattle slurry and manure. After physiological characterization of the isolates, sixteen strains (representatives of Bacillus, Providencia and Ochrobactrum genera) were chosen for the construction of a Microbial Consortium with High Cellulolytic Activity, called MCHCA. The selected strains had a high endoglucanase activity (exceeding 0.21 IU/mL CMCase activity) and a wide range of tolerance to various physical and chemical conditions. Lab-scale simulation of biogas production using the selected strains for degradation of maize silage was carried out in a two-bioreactor system, similar to those used in agricultural biogas plants. The obtained results showed that the constructed MCHCA consortium is capable of efficient hydrolysis of maize silage, and increases biogas production by even 38%, depending on the inoculum used for methane fermentation. The results in this work indicate that the mesophilic Microbial Consortium with High Cellulolytic Activity has a great potential for application on industrial scale in agricultural biogas plants.